(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This research paper explores the implementation of a high availability solution for SAP HANA Database 1.0 SP12 and SAP ASCS/ERS (ABAP Central Services/Enqueue Replication Server) using the Pacemaker clustering tool. The study focuses on the architecture, configuration, and best practices for setting up a robust failover mechanism to ensure continuous operation of critical SAP systems. By examining the integration of SAP HANA’s system replication capabilities with Pacemaker’s cluster management features, this paper provides insights into creating a resilient SAP environment capable of minimizing downtime and maintaining data consistency during failover events.